The Existence and Effect of Dark Energy Redshift on Cosmological Age - Riccardo C. Storti (Advances in Astronomy)
A derivation of Cosmological Age explicitly constrained by Cosmic Microwave Background Radiation (CMBR) is presented, demonstrating that the correct value of Cosmological Age is equal to the Hubble Age. It is shown that utilizing “z = 0” for Cosmological Redshift in the Present Epoch introduces a fundamental flaw into Cosmological Age calculations. However, this flaw is captured and corrected by the Polarizable-Vacuum (PV) Model of Gravity developed by Puthoff, suggesting that the Dark Energy Field exists as a massive photonic field. Consequently, it is demonstrated that for a Dark Energy Driven description of Accelerated Cosmological Expansion, Cosmological Redshift takes a negative value in the Present Epoch.